Model Integrasi Pendidikan Agama Hindu Dalam Pengembangan Pariwisata Spiritual Regeneratif Di Desa Wisata Gunung Salak Bali - Pradna Lagatama; Nyoman Danendra Putra (Jayapangus Press, 2026)
The development of spiritual tourism in Bali faces challenges related to cultural commodification and the desacralization of religious practices due to the increasing economic orientation of tourism activities. This condition highlights the importance of strengthening Hindu religious education values as a foundation for sustainable and regenerative spiritual tourism development. This study aims to analyze the integration model of Hindu religious education in the development of regenerative spiritual tourism in Gunung Salak Tourism Village, Bali. The research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and document analysis involving eight purposively selected informants and were analyzed using thematic analysis supported by source and method triangulation. The findings reveal that Hindu religious education values, particularly Tri Hita Karana, Tat Twam Asi, and Tri Kaya Parisudha are integrated into community spiritual practices, community-based tourism management, and destination governance oriented toward cultural and environmental preservation. The study proposes an integrative model that connects Hindu religious education as a value foundation, community spiritual practices as the basis of tourism experiences, community-based tourism management as the implementation mechanism, and regenerative tourism principles as the framework for destination development. The model contributes to cultural preservation, the strengthening of spiritual awareness, increased community participation, and the social and ecological sustainability of the tourism village. It can be concluded that Hindu religious education plays a strategic role as both a normative and transformative foundation in fostering regenerative spiritual tourism that is harmonious, educational, and sustainable.